2015
DOI: 10.3892/mmr.2015.4544
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide attenuates doxorubicin-induced cardiotoxicity by inhibiting the expression of peroxiredoxin III in H9c2 cells

Abstract: Doxorubicin (DOX) is a widely used chemotherapeutic agent, which can give rise to severe cardiotoxicity, limiting its clinical use. Preliminary evidence suggests that hydrogen sulfide (H2S) may exert protective effects on DOX‑induced cardiotoxicity. Therefore, the aim of the present study was to investigate whether peroxiredoxin III is involved in the cardioprotection of H2S against DOX‑induced cardiotoxicity. The results demonstrated that DOX not only markedly induced injuries, including cytotoxicity and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Recently, exogenously delivered H 2 S and/or enhancement of the endogenous H 2 S signaling pathway has been shown to limit cardiac injury acutely after I/R injury . Indeed, it has been demonstrated that H 2 S has effects on INF sparing after I/R injury but is also able to exert potent antioxidant, antiapoptotic, anti‐inflammatory, and proangiogenic effects under various stressors. In addition, the biological profile of H 2 S is similar to that of NO, and these 2 endogenous gaseous signaling molecules may affect one another with respect to their production and cell signaling molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, exogenously delivered H 2 S and/or enhancement of the endogenous H 2 S signaling pathway has been shown to limit cardiac injury acutely after I/R injury . Indeed, it has been demonstrated that H 2 S has effects on INF sparing after I/R injury but is also able to exert potent antioxidant, antiapoptotic, anti‐inflammatory, and proangiogenic effects under various stressors. In addition, the biological profile of H 2 S is similar to that of NO, and these 2 endogenous gaseous signaling molecules may affect one another with respect to their production and cell signaling molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they observed that selectively inhibiting ERK1/2 could further obtain the above-mentioned effects of H 2 S. Liu and his colleagues also found that doxorubicin could induce cytotoxicity through increasing the peroxiredoxin III expression. They pretreated H9c2 cells with NaHS and found that the cell viability was increased, cell apoptosis attenuated, and the peroxiredoxin III overexpression reversed (Liu et al, 2016a ). Therefore, H 2 S might play an antioxidant role in doxorubicin-induced cardiotoxicity via inhibiting ROS generation, ER stress-related proteins levels, peroxiredoxin III expression, and ERK1/2 phosphorylation and activating Nrf2 and its downstream pathway.…”
Section: Protective Mechanisms Of H 2 S In Chemothmentioning
confidence: 99%
“…Once produced, H 2 S is broken down rapidly and participates in many pathophysiological processes (Tang et al, 2006 ; Du et al, 2011 , 2014 ; Sun et al, 2011 ; Altaany et al, 2014 ; Yang and Wang, 2015 ; Bian et al, 2016 ; Cao and Bian, 2016 ; Panthi et al, 2016 ). More importantly, recent evidence shows that H 2 S may play cytoprotective role in heart diseases (Shen et al, 2015 ; Liu et al, 2016a ; Szabo, 2016 ; Huang et al, 2017 ). Here, we mainly reviewed the cardioprotective role of H 2 S in chemotherapy and its possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…One of our previous studies also found that H S also improved diabetic myocardial fibrosis, which is associated with the inhibition of oxidative stress [ 31 ]. In an experiment in vitro , H S was also found to improve the cardiotoxicity of doxorubicin, and H S sustained release agent Diallyl trisulfide inhibited doxorubicin-induced myocardial apoptosis [ 13 , 14 ]. The results of this experiment revealed that after the intervention with H S donor NaHS, the cardiac function of the rats in the DOX+H S group was improved, EF and FS were increased, LVEDD and LVESD were significantly decreased, and HW/BW was significantly decreased, compared with DOX group.…”
Section: Discussionmentioning
confidence: 99%
“…The role of gaseous signal molecule H S in doxorubicin-induced myocardial fibrosis in rats and its internal mechanism has been rarely studied. Some studies have revealed that H S can relieve doxorubicin-induced myocardial damage, thereby improving the cardiac function of doxorubicin-induced myocardial fibrosis in rats [ 13 , 14 ]. Thus, we assume that H S may improve doxorubicin-induced myocardial fibrosis in rats, and the relevant mechanism may be correlated with the inhibition of oxidative stress, inflammatory response, and apoptosis by regulating the Keap1-Nrf2 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%